2019
DOI: 10.1101/680181
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Endometrial Transcriptome and Progesterone Receptor Cistrome Reveal Important Pathways and Epithelial Regulators

Abstract: 1 9 2 0

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 101 publications
(90 reference statements)
1
17
0
Order By: Relevance
“…PR-A and PR-B form homodimers or heterodimers [ 85 ], and PR-A exerts dominant negative effects on PR-B mediated transcription [ 86 ]. ChIP-seq analyses of human endometrium [ 87 ] and mouse uterus and ovary [ 88 ] revealed that PRs exert genomic action by binding progesterone response elements (PREs) or other transcription factor binding motifs. Nongenomic effects of PRs are also reported, which are mediated by the interaction of a proline-rich sequence motif within PRs and SRC homology 3 (SH3) domain in Src family tyrosine kinases leading to the activation of Src family tyrosine kinases [ 89 ].…”
Section: Prs In the Regulation Of Mitochondrial Oxphos Complexesmentioning
confidence: 99%
“…PR-A and PR-B form homodimers or heterodimers [ 85 ], and PR-A exerts dominant negative effects on PR-B mediated transcription [ 86 ]. ChIP-seq analyses of human endometrium [ 87 ] and mouse uterus and ovary [ 88 ] revealed that PRs exert genomic action by binding progesterone response elements (PREs) or other transcription factor binding motifs. Nongenomic effects of PRs are also reported, which are mediated by the interaction of a proline-rich sequence motif within PRs and SRC homology 3 (SH3) domain in Src family tyrosine kinases leading to the activation of Src family tyrosine kinases [ 89 ].…”
Section: Prs In the Regulation Of Mitochondrial Oxphos Complexesmentioning
confidence: 99%
“…The molecular protagonists in the decidualization route are P4 and cAMP [29]. The PGR-regulated genes and pathways include HOXA10, HAND2, IGFBP-1, and BMP2; ERK/MAPK, WNT/ß-catenin, and IHH-COUPTFII pathways [35]. HOXA10 is a PGR target in the endometrium and has been reported to in uence WNT4 expression around the implantation site in mice [36].…”
Section: Wnt/ß-catenin Signaling Pathwaymentioning
confidence: 99%
“…To identify the gene networks functioning at the TE-EEC interface, we used single-cell transcriptomic datasets from blastocyst TE (Petropoulos et al 2016), and bulk transcriptomic data from EEC directly isolated from endometrium (Chi et al 2020). Cell surface or secreted genes, differentially expressed in receptive (mid-secretory phase) vs non-receptive (proliferative phase) endometrial epithelium ( Figure S2A), were used to identify 39 cognate cell surface genes in day 6 TE.…”
Section: Gene Network At the Te-eec Interfacementioning
confidence: 99%
“…All in silico modelling and analysis was performed in R version 3.4.2 (R Foundation for Statistical Computing). Differentially expressed genes (DEGs) were defined by ANOVA (cutoff p<0.01) between proliferative phase (n=4) and mid-secretory phase (n=4) endometrial epithelial RNA sequencing (RNAseq) transcriptomes (GEO Accession GSE132711) (Chi et al 2020). Localisation of the protein products of these genes was investigated using the Database for Annotation, Visualisation and Integrated Discovery (DAVID) (Huang da et al 2009a, Huang da et al 2009b.…”
Section: Modelling the Te-eec Interface In Silicomentioning
confidence: 99%
See 1 more Smart Citation